Preliminary - Gómez-Botero, Maryory Astrid (Revista Facultad de Ingeniería Universidad de Antioquia, 2015)
After some decades using a standard design, the Revista Facultad de Ingeniería Journal’s appearance has been improved, for both printed and digital versions. A new modernized logo is being released in the current issue, simplifying the name of the journal to a single term easily to pronounce: REDIN. The new layout includes a color triad in the front cover, an image on the book cover which, in some cases, may correspond to an image of one of the papers published in the issue (with the permission of the authors), and in some other cases may be an image designed only for the purpose of the cover. Moreover, on the front cover, the seal of the University of Antioquia is included and two prominent papers in the issue recommended by the editors are highlighted. The back cover preserves the content: the issue, the indexed bibliographic databases, and the bar code used in electronic publishing. After this issue, at the bottom of the fi rst page of each article the Creative Commons Attribution copyright license icon is embraced, in order to inform users and, at the same time, to protect the journal from legal implications in case of misuse by a user of the material published in the journal. As our readers can verify, the paper presentation style has a modernized format allowing readers to easily access the information using the numbering in all sections of the paper.